Microwave Imaging Technique for Detection of Multiple Line Cracks in Concrete Material - Jiya, E.A.; Anwar, N.S.N.; Bala, S.A.; Bello, E. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Nowadays, many concrete structures are exposed to higher loads than they are designed for due to the increase in human population and uncertain environmental conditions. This leads to a faster deterioration of the structure for example formation of cracks. Cracks provide significant signs for the health and residual strength of a civil structure. Though they appear at times in form of lines, they cannot be easily identified or detected by traditional methods and techniques. For example, manual inspection is too costly in terms of time and effort; meanwhile, other non-destructive techniques are bounded by each unique weaknesses. This research proposes a microwave imaging technique with ultra-wideband (UWB) signal in detecting multiple line cracks. Various crack scenarios were first simulated using Finite-Difference Time-Domain (FDTD) to see the performance of the proposed technique. Delay-And-Sum algorithm is used for image reconstruction. This technique was able to detect single, double, three and multiple line cracks on single brick of size 2 mm accurately. Notwithstanding, more than three cracks on a single brick could not be detected as they appear as a clutter. In conclusion, the proposed technique is useful for crack detection in building and man-made structures.